T Cells From CLL Patients Recognize Spontaneously Peptides Derived of the Receptor Tyrosine Kinase Ror1 - -Farsangi, Mohammad Hojjat; Daneshmanesh, Amir Hossein; Jeddi-Tehrani, Mahmood; Osterborg, Anders; Shokri, Fazel; Mellstedt, Håkan; Rabbani, Hodjattallah (BLOOD, 2010)
Abstract 3603 The receptor tyrosine kinase Ror1 is a tumor-associated molecule over-expressed in chronic lymphocytic leukemia (CLL) and a variety of other malignancies with potential implication for targeted immunotherapy. Little is known about the functional role of Ror1 in the leucomogenesis of CLL. Aims: To assess spontaneous T cell response against Ror1 in CLL patients. Autologous T cell response against Ror1 was studied in 9 CLL patients and 6 healthy subjects expressing the HLA-A2 allele. Four synthetic 9-mer HLA-A2 restricted peptides selected from different parts of the Ror1 molecule were loaded on dendritic cells and co-cultured with enriched autologous T cells. T cell response was determined by enumeration of the frequency of IFN-γ, IL-5 and IL-17A secreting T cells by ELISPOT. Cell proliferation was determined by 3H-thymidine incorporation. Our results demonstrated a significantly higher frequencies of IFN-γ producing T cells (p<0.05-0.0001) and to a lesser extent IL-17A secreting autologous T cells (p<0.05) in response to Ror1 peptides in CLL patients compared to healthy controls. No IL-5 secreting T cells were noted. The frequency of IFN-γ secreting T cells was significantly higher in non-progressive as compared to progressive CLL patients (P<0.05). No differences were observed between patients with mutated and unmutated immunoglobulin heavy chain variable region (IGHV) genes. Ror1 may spontaneously induce mainly a type 1 T cell response in CLL patients, particularly in those with non-progressive disease as compared to progressive disease. Ror1 may be an immunodominant antigen in CLL which, has also been suggested by Fakuda et al. PNAS, 105, 3047, 2008. Active immunotherapy using Ror1 as a target might be an interesting approach to test in the clinic. No relevant conflicts of interest to declare.